THE DOCTORATES IN COLOMBIA. Legislation, dayliness and construction of identities - Soto Arango, Diana Elvira (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2011)
Doctorates in Colombia intending research development are of recent creation  mostly at the end of the XX century. These have been originated on account of both the university conception change and the knowledge globalization. In Colombia, Doctorates present an exuberant legislation in the XXI century, which is away from the educational reality that is not able to be transformed. As a matter of fact, Doctorates in education have been created with the organizational peculiarity of academic Nets. In the case of RUDECOLOMBIA, since the identity construction of the Net, it is projected with educational regional development objectives and with projects og nation construction.